Influence of music and its genres on respiratory rate and pupil diameter variations in cats under general anaesthesia: contribution to promoting patient safety. Issue 2 (February 2016) - Mira, Filipa; Costa, Alexandra; Mendes, Eva; Azevedo, Pedro; Carreira, L Miguel
Objectives: The aims of the study were to recognise if there is any auditory sensory stimuli processing in cats under general anaesthesia, and to evaluate changes in respiratory rate (RR) and pupillary diameter (PD) in anaesthetised patients exposed to different music genres, while relating this to the depth of anaesthesia. Methods: A sample of 12 cats submitted for elective ovariohysterectomy was exposed to 2 min excerpts of three different music genres (classical [CM], pop [PM] and heavy metal [HM]) at three points during surgery (T1 = coeliotomy; T2 = ligature placement and transection of the ovarian pedicle; T3 = ligature placement and transection of the uterine body). A multiparametric medical monitor was used to measure the RR, and a digital calliper was used for PD measurement. Music was delivered through headphones, which fully covered the patient's ears. P values   <0.05 were considered to be statistically significant.    Results: Statistically significant differences between stimuli conditions for all surgical points were obtained for RR (T1, P = 0.03; T2, P = 0.00; T3, P = 0.00) and for PD (T1, P = 0.03; T2, P = 0.04; T3, P = 0.00). Most individuals exhibited lower values for RR and PD when exposed to CM, intermediate values to PM and higher values to HM. Conclusions and relevance: The results suggest that cats under general anaesthesia are likely to perform auditory sensory stimuli processing. The exposure to music induces RR and PD variations modulated by the genre of music and is associated with autonomic nervous system activity. The use of music in the surgical theatre may contribute to allowing a reduced anaesthetic dose, minimising undesirable side effects and thus promoting patient safety.